The relationship of leadership styles towards organizational commitment among employees: an emperical study at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) / Nurul Najwa Mohd Hassan - Mohd Hassan, Nurul Najwa (2015)
The study is an attempt to determine the relationship between leadership styles towards organ izational commitment among employees at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT).This study covered 144 official employees out of 241 from 14 departments and respondents need to fill up the questionnaires given to them. Resu lts indicated that respondents received the combination of Transformational Leadersh ip, Transactional Leadership and Laissez Faire Leadership Style and they show high organizational commitment and loyal to the organization.The highest leadership style that perceived in the organization 1s laissez faire leadership style. Findings are discussed further in this report.